2020
DOI: 10.3390/nano10020200
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Nano-MoS2 Quantum Dots as Liquid Lubricant Additive for Tribological Behavior Improvement

Abstract: Molybdenum disulfide quantum dots (MoS2 QDs) are a promising lubricant additive for enhanced engine efficiency. In this study, MoS2 QDs were used as lubricating oil additives for ball-on-disc contact and had adequate dispersity in paroline oil, due to their super small particle size (~3 nm). Tribological results indicate that the friction coefficient of paroline oil with 0.3 wt.% MoS2 QDs reached 0.061, much lower than that of pure paroline oil (0.169), which is due to the formation of a stable tribo-film form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 30 publications
1
35
0
2
Order By: Relevance
“…Research in this area has looked for ways to increase the wear resistance of solid lubricant coatings at different contact loads and over a relatively wide range of temperatures and air humidity. Moreover, researchers have sought to find fundamentally new forms/structural states that can lead to new properties [11][12][13][14]. The testing temperature range has been, as a rule, between room temperature and~500 • C. In most cases, coatings were applied through ion (magnetron) sputtering [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Research in this area has looked for ways to increase the wear resistance of solid lubricant coatings at different contact loads and over a relatively wide range of temperatures and air humidity. Moreover, researchers have sought to find fundamentally new forms/structural states that can lead to new properties [11][12][13][14]. The testing temperature range has been, as a rule, between room temperature and~500 • C. In most cases, coatings were applied through ion (magnetron) sputtering [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The elemental analysis of black sediments reveals that the main element of black sediments is C (Figure 8(b)). It is well known that C element can be resulted from the carbon deposition due to the combustion of furl or lubricating oil, but it has been reported that the occurrence of carbon deposition needs a temperature higher than 300℃ [45]. As the test was performed at the temperature of 150℃, it is considered that the observed black sediments mainly come from the ND composite.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the wear test research can be seen in Figure 3. The graph shows the same trendline as Figure 2, namely the greater the viscosity value of a lubricant, the lower the wear value [16][17][18][19][20][21].…”
Section: A the Effect Of Lubricant Variation On Viscosity And Coeffimentioning
confidence: 89%
“…Table 1. Variations in viscosity and coefficient of friction and wear rates [16][17][18][19][20][21] Research on the correlation between the viscosity of 100 O C (cSt) and the coefficient of friction (coF) can be seen in Figure 2. The graph shows that the greater the viscosity value of a lubricant causes the lower friction coefficient value.…”
Section: A the Effect Of Lubricant Variation On Viscosity And Coeffimentioning
confidence: 99%